The Analysis Study of Risk of Bleeding in Patients Undergoing Pulmonary Procedure on Antiplatelet or Anticoagulant: A Comprehensive Systematic Review - Adityawan, Yusuf Candra; Al Mubarok, Toha (The International Journal of Medical Science and Health Research, 2024)
Background: Pumonary procedure is considered to be a low bleeding risk procedure, platelet count and coagulation profile are usually evaluated prior to the procedure. In addition, several society guidelines recommend holding antiplatelet medications such as clopidogrel and prasugrel for 5 days prior to the procedure as well as holding one dose of unfractionated heparin prior to pulmonary procedure. The aim: The aim of this study to show about risk of bleeding in patients undergoing pulmonary procedure on antiplatelet or anticoagulant. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Pulmonary procedure on patients receiving either antiplatelet or anticoagulation therapy using the best available evidence. With this knowledge, physicians can assist patients or their substitute decision-makers in making an informed decision regarding the timing and safety of proceeding with a pulmonary procedure.